Dimensi Psikologis dan Kepribadian yang Terbentuk dari Ibadah Umrah - Rahman, Anisa Hayati; Lubis, Ramadan (MODELING: Jurnal Program Studi PGMI, 2023)
Umrah is a worship that has a very high spiritual value, both culturally and spiritually. With the large number of pilgrims performing the Umrah pilgrimage, it is also important to discuss the meaning of the Umrah pilgrimage itself, therefore this research aims to find out more deeply how the psychological and personality dimensions are formed from the Umrah pilgrimage. The method used in this research is library research or literature study, which utilizes sources from books, journals, documents and others as material for the material to be explained. Based on the research, it was found that it is important to know how the psychological dimensions are contained and what personality is formed from the Umrah pilgrimage.